The Effect of Local Taxes and Local Levies on the Level of Local Financial Independence in Regency/City in Riau Province in Fiscal Year 2019-2024 - Mailani Mailani; Husnul Muttaqin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the impact of regional levies and taxes on the degree of regional financial independence in Riau Province's cities and regencies. Using secondary data from the Directorate General of Financial Balance (DJPK) for the years 2019–2024, this study employs a quantitative approach. Classical assumption tests, including autocorrelation, heteroscedasticity, multicollinearity, and normality tests, were used to analyze the data. tests for multiple linear regression and hypothesis testing, including the t-test, F test, and determination coefficient test (R2). The study's findings demonstrate that the degree of regional financial independence is positively and significantly impacted by partially regional taxes. Additionally, regional levies have a favorable and substantial impact. The degree of regional financial independence is significantly impacted by both of these factors at the same time. These results demonstrate how tax and levy optimization may boost regional fiscal independence and Regional Original Revenue (PAD).